PEMANFAATAN LIMBAH MINYAK JELANTAH DALAM PEMBUATAN SABUN BATANG BERSAMA BANK SAMPAH BUNGA RAYA, PURBAYAN, KECAMATAN BAKI, KABUPATEN SUKOHARJO, JAWA TENGAH - Henny Parida Hutapea; Yulia Shara Sembiring; Himmah Sekar Eka Ayu Gustiana (Unika Santu Paulus Ruteng, 2022)
Utilization of used cooking oil in the manufacture of bar soap is one way of engineering waste products in reducing environmental pollution which will increase the economic value of a product. The purpose of this community service is to increase creativity and innovation for related partners, namely members of the Bunga Raya Waste Bank in processing used cooking oil waste into bar soap products. The method of activity is that it begins with socialization and discussion, followed by training for partners by creating small groups so that each member can be directly involved and it is easier to understand how it is made and ends with evaluation. The result of this service activity is that each member can make bar soap using used cooking oil. This bar soap is very promising to be used as a micro-enterprise by partners, namely members of the Bunga Raya Waste Bank which is a community forum that helps handle waste processing. It is hoped that through this training, the Bunga Raya Waste Bank can also provide the knowledge it gains to the community to care about the environment by processing waste into a useful product